Analysis Of The Role Of Management In The Implementation Of CP DBD In Inpatient Children At Hospital X - Lia Sarita Ristiyana; Sutopo Patria Jati; Septo Pawelas Arso (Green Publisher Indonesia, 2024)
This study investigates the implementation of clinical pathways (CPs) for pediatric Dengue Hemorrhagic Fever (DHF) inpatients at Hospital X, a Type C hospital in Indonesia, focusing on the role of management in CP development and compliance. Clinical pathways aim to enhance hospital efficiency, quality of care, and patient satisfaction. However, the study identified several issues in CP implementation, including incomplete documentation, lack of socialization and training among staff, and inadequate managerial involvement in CP development and oversight. Data were collected through in-depth interviews with attending physicians, nurses, pharmacy staff, and medical management, along with analysis of 53 pediatric DHF CPs. Results showed that CP compliance rates were below 80%, and the hospital's organizational role in CP development, as assessed by the ICPAT dimension 6 instrument, was insufficient. Key areas of non-compliance included lack of evidence of clinical governance, integration with other hospital initiatives, and adequate support for CP documentation and variation reporting. Recommendations include increasing management involvement, providing comprehensive training for staff, and implementing regular CP evaluations. The findings highlight the need for stronger multidisciplinary collaboration and hospital management support to optimize CPs, ensure compliance, and improve service quality.